Selection of product design configuration for improved sustainability using the product sustainability index (prodsi) scoring method - Hassan, M. F. (2013)
Generating new variants for design elements of products, structuring them into a complete configuration and evaluating the alternate configurations are essential for product design. Evaluating the likely product configurations in terms of sustainability aspects continues to become a useful aspect of interest to product designers. This paper proposes a new approach for applying the Product Sustainability Index (ProdSI) in selecting the best possible configurations for product design. In this paper, the recently developed ProdSI methodology is used to evaluate sustainability performance of a product. The approach is useful for product designers to generate numerous likely product design configurations and subsequently select the most sustainable product design configuration. An example of an armed-chair is used to illustrate the proposed new approach.